2017
DOI: 10.1186/s12933-017-0531-9
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end-products decreases expression of endothelial nitric oxide synthase through oxidative stress in human coronary artery endothelial cells

Abstract: BackgroundAdvanced glycation end-products (AGEs) are elevated under diabetic conditions and associated with insulin resistance, endothelial dysfunction and vascular inflammation in humans. It has been demonstrated that AGEs evoke oxidative and inflammatory reactions in endothelial cells through the interaction with a receptor for AGEs (RAGE). Here, we aimed to identify the cellular mechanisms by which AGEs exacerbate the endothelial dysfunction in human coronary artery endothelial cells (HCAECs).Methods30 type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 41 publications
1
90
0
Order By: Relevance
“…The increased ROS production accelerates telomere shortening, induces the DNA damage response (DDR), and causes senescence growth arrest . Ren et al have shown that diabetic conditions impaired the function of endothelial cells through oxidative stress . Furthermore, Chen et al have reported that in a HG environment, endothelial cells exhibited a senescence‐associated secretory phenotype (SASP) by upregulating the NOX‐derived ROS pathway .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased ROS production accelerates telomere shortening, induces the DNA damage response (DDR), and causes senescence growth arrest . Ren et al have shown that diabetic conditions impaired the function of endothelial cells through oxidative stress . Furthermore, Chen et al have reported that in a HG environment, endothelial cells exhibited a senescence‐associated secretory phenotype (SASP) by upregulating the NOX‐derived ROS pathway .…”
Section: Discussionmentioning
confidence: 99%
“…HG environment has been suggested to cause increased production of free radicals and consequently accelerate aging progress . Existing evidence confirms a prominent role for reactive oxygen species (ROS) as mediators of cellular aging in diabetes . Li et al have reported that HG induced fibroblast senescence in a time‐ and dose‐dependent manner .…”
Section: Introductionmentioning
confidence: 99%
“…In vascular smooth muscle cells, incubation with AGEs has been shown to stimulate L‐type calcium channels, causing an increase in ROS and activation of both ERK and NF‐kB, potentially leading to an increase in cardiovascular disease risk (Molinuevo, Fernández, Cortio, McCarthy, & Sedlinsky, ). Similarly, in human coronary artery endothelial cells, incubation with AGEs, at concentrations found in diabetic patients, decreased the expression of endothelial nitric oxide synthase and nitric oxidize production, along with inducing oxidative stress (Ren et al., ). In experimental fatty liver disease model mice, a diet with high AGE content increased hepatic AGE content, increased NADPH‐dependent superoxide production, and exacerbated liver injury through an increase in oxidative stress and interaction with profibrotic cellular receptors (Leung et al., ).…”
Section: Ages and Their Association With Diseasementioning
confidence: 94%
“…() associated high serum methylglyoxal, an AGE precursor, with a faster decline in attention span in elderly people (average of 71 y of age). In type 2 diabetic patients with coronary artery atherosclerosis, serum levels of AGEs were found to be inversely correlated with endothelial function (Ren et al., ). In their study of AGEs and incident cardiovascular events in patients with type 2 diabetes, Koska et al.…”
Section: Ages and Their Association With Diseasementioning
confidence: 99%
“…Therefore, increased ROS and oxidative stress impair deoxyribonucleic acid, lipid, protein, as well as mitochondrial function. Recent data further support that increased ROS decreases bioavailable NO and thus impairs arterial relaxation [34]. Recent research has also shown that enhanced EC specific MR activation promotes oxidative stress, vascular fibrosis, increased arterial stiffness, and impairment of flow-mediated mesenteric artery relaxation [25].…”
Section: Pathological Mechanisms Of Excessive Arterial Stiffnessmentioning
confidence: 97%